Changing dimensions of Community Forestry in Nepal: From subsistence towards sustainability - Giri, Kalpana (Nepal Journal of Forestry, 2008)
The two decades of community forest management witnesses tremendous shifts in forest policies and procedures in Nepal. This runs parallel with the changing objectives of forest management from subsistence to sustainable economic transforms. This paper reviews the changing context and needs of forest management and analyses the issues and challenges from policy to practice.Keywords: Resource, subsistence, poverty, sustainable development, externality, governance